Transforming virtual world learning - Hinrichs, Randy J.; Wankel, Charles (Bingley, U.K. : Emerald, 2011)
This book is a practical guide on how to transform your ideas from virtual world course ware to virtual world learning experiences. The book argues that setting up learning in 3D virtual worlds requires a transformative approach. The advice given in this book comes from real world implementers of virtual world learning. The models presented here show how to transform your thinking in 3D spaces and achieving your organizational learning goals while motivating your learners. The practical articles and lesson plans come from those pioneers who have used virtual worlds to learn, teach and support their learners with in-world presence. Transforming starts with recognizing virtual worlds as a place, and then using the space to plan in 3D, design real-time and implement a'virtual biodome effect' for continuous learning. It is our hope the book inspires current educational institutions to think about creating persistent, scalable communities that thrive on communication, global collaboration and sustainable interactivity. The results are the same for K-12, community college, university, industry and lifelong learners. It's not just about being in a virtual world, it's about doing something engaging there to educate and entertain the work force of the interconnected internet.
Introduction : thinking in 3D / Randy Hinrichs -- A cybergogy of learning archetypes and learning domains : practical pedagogy for 3D immersive virtual worlds / Lesley Scopes -- Initial teacher training in a virtual world / John Woollard -- Faculty development for and in virtual worlds / Jennifer L.V. Sparrow, Samantha J. Blevins, Aimee M. Brenner -- Pre-service teachers' teaching practice in Second Life{u0BE0}Donguk Cheong, Youngkyun Baek, Hoe Kyeung Kim -- A practical model and assignments for using virtual worlds in higher education / Dona Cady, Matthew Olson, Peter Shea, J.M. Grenier -- Instructional design frameworks for Second Life{u0DA9}rtual learning / Scott J. Warren, Jenny S. Wakefield -- Using the community of inquiry (CoI) model and Bloom's revised taxonomy to support 21st century teaching and learning in multi-user virtual environments / Melissa L. Burgess, Phil Ice -- Marinetta Ombro : a culture not a classroom / Owen Kelly -- Enhancing graduate courses through educational virtual tours / Irena Bojanova, Les Pang -- Using problem-based learning within 3D virtual worlds / Vanessa Parson, Simon Bignell -- Intercultural collaborative learning in virtual worlds / Btrice S. Hasler -- Alice's adventures in programming narratives / Reneta D. Lansiquot, Candido Cabo -- Teaching higher education students with diverse learning outcomes in the virtual world of Second Life{u0BE0}Sue Gregory.
Includes index.
Keywords: Education, Higher -- Computer-assisted instruction; Shared virtual environments; Computer-assisted instruction